An Active Inductor Based Low Noise Amplifier for RF Receiver - Aljarajreh, H.; Reaz, M. B. I.; Amin, M. S.; Husain, H. (Elektronika ir Elektrotechnika, 2013)
Low Noise Amplifier (LNA) is a significant part in Radio Frequency (RF) receivers and plays a key role in the chip size and the implementation cost. An LNA for RF receivers utilizing the active inductor is presented. The proposed design is an alternative solution to overcome the usage of passive inductors to reduce the chip area. Besides, the active inductor reduces the parasitic capacitors affect at high frequencies. Designed in 0.18-μm CMOS process, the LNA achieves a voltage gain of 20dB, a minimum Noise Figure (NF) of 3.1 dB with low power consumption and good input and output impedance matching at 2.45 GHz. With 0.003 mm2 chip area, the proposed design is suitable for portable wireless communication devices. DOI: http://dx.doi.org/10.5755/j01.eee.19.5.2158